Portal vein omentin is increased in patients with liver cirrhosis but is not associated with complications of portal hypertension. (16th July 2013) - Eisinger, Kristina; Krautbauer, Sabrina; Wiest, Reiner; Karrasch, Thomas; Hader, Yvonne; Scherer, Marcus N.; Farkas, Stefan; Aslanidis, Charalampos; Buechler, Christa
Abstract Background Omentin is a visceral fat–derived adipokine associated with endothelium‐dependent vasodilation. Impaired endothelial function is a major cause of portal hypertension in liver cirrhosis. The aim was to assess associations of omentin with systemic markers of endothelial function, namely arginine and asymmetric dimethylarginine (ADMA) and complications of portal hypertension in liver cirrhosis. Materials and methods Systemic omentin was measured by ELISA in portal venous serum (PVS), systemic venous serum (SVS) and hepatic venous serum (HVS) of 40 patients with liver cirrhosis and 10 liver‐healthy controls. ADMA and arginine were determined in SVS of the patients by ELISA. Results Omentin is elevated in PVS and tends to be increased in SVS and HVS of patients with liver cirrhosis compared with controls. Omentin is principally expressed in visceral fat, and PVS omentin tends to be higher than SVS levels. Lower HVS than PVS omentin suggests that omentin may be partly removed from the circulation by the liver. Omentin in serum is not associated with stages of liver cirrhosis defined by CHILD‐POUGH or MELD score and is not affected in patients with ascites. HVS omentin tends to be reduced in patients with large varices compared with patients without/with small varices. Arginine/ADMA ratio is reduced in patients with massive ascites but is not associated with variceal size. Further, Arginine/ADMA ratio does not correlate with omentin. Conclusion Current data show that PVS omentin is increased in liver cirrhosis but is not associated with complications of portal hypertension.